Dukungan Sosial dan Job Burnout Pengaruhnya Terhadap Kinerja Polisi (Studi Kasus Pada Anggota Kepolisian Polrestabes Bandung) - Muhamad Husnul Rizqi; Agus Riyanto (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2021)
This research has a purpose was to determine the effect of social support and burnout on police performance at Polrestabes Bandung both descriptively and verification consisting of simultaneous and partial. There is a population of 296 members of the Bandung Police Satsabhara Polrestabes and 75 respondent were abtained using the slovin method, using multiple linier regression analysis, classical assumption test, and hypothesis testing. which were tested using SPSS 25 for window application, and police performance are descriptive analysis, it is explained that social support, job burnout, and police performance are in the good category, the results of the verification analysis prove that social support significantly & positively affects police performance, while job burnout significantly & negatively affects police performance, then social support and job burnout simultaneously affect police performance.